PLAYING WITH THE COLORS-PRE-SCHOOL CHILDREN’S SELF-DIRECTED DRAWING EXPERIANCE - Randoha, Antra (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
At the pre-scool age, playing is the main key to the child’s way to express them selfs in drawing process. In order to ensure the self-directed drawing, there is a need for the availability of diverse naterials throughout of the day, enabling the child to act and play in accordance with his intentions. In a drawing process, trying out different techniques, tools,mixing colors, trying to discover new ways of expression, observing and imitating other (children’s or adult) actions, provides the basic conditions for meaningful activity of a child. The aim of the thesis is to find out theoretically and practically the essence of self-directed drawing activity of preschool children and possibilities of the improvement of it in the pedagogical process. Materials and methods. Used the analysis of pedagogical and psychological literature on the possibilities of self-management skills development in the pedagogical process - drawing and accomplished pegogical observation. Results. The essence of self-directed drawing activity of preschool children was updated and possibilities of improvement reviewed .